Enabling Access to Federated Grid Databases: An OGSA-DAI ODBC Driver - Lloyd, Ashley; Jackson, M.; Sloan, T. (EPSRC, 2005)
Access to distributed heterogeneous data resources is possible through Grid middleware such as OGSA-DAI (Open Grid Services Architecture Data Access and Integration) which is designed to assist with the integration of data from separate resources via Web services. This paper reports on the INWA project's investigations into whether OGSA-DAI can be exposed as an ODBC data source and used as a back-end to existing, popular data extraction and processing programs that are ODBC-compliant. This capability would provide additional location and product transparency for the data resources used by these programs. It also opens up the possibility of allowing these programs to extract data from federated data resources or "virtual databases".